Economic Growth And Human Development In Indonesia - Burhanudin, Burhanudin; Susilastuti, Darwati; Sugiyanto, Sugiyanto (PT Maju Malaqbi Makkarana, 2025)
The need for a good understanding of economic growth and human capital as a measure of human development is an important concern in national development. Both sectors play an important role in formulating economic development policies and human development as a whole, as evidenced by Indonesia. Therefore, this article empirically analyzes the contribution of economic growth to the human development index in Indonesia. Linear regression analysis of panel data through the Redundant Fixed Effect Model Test approach and the Hausman Test is used to test the extent to which the panel data estimation model can explain the effect of economic growth on human development in Indonesia. These two approaches produce a Fixed Effect Model that shows that the effect of economic growth contributes strongly to human development in Indonesia. Economic growth has a positive and significant impact on the Human Development Index. During the testing period, economic growth showed an increase and a positive direction towards human development, even though the economy was in a state of the COVID-19 pandemic. The Indonesian economy continues to grow strongly in the face of various conditions, including the Covid-19 pandemic, as well as human development continues to show an increase, as evidenced by the human development index, which continues to increase.